Methods to improve electro kinetic energy conversion efficiency in nanoscale channel - P Nair, Manu; S Babu, Jeetu (International Journal of Engineering and Technology, 2018)
With the help of MD simulation in a Lennard jones system, Argon fluid flowing through a Platinum channel, we have demonstrated a practical approach to tune slip length in nanoscale flows. It was found that the presence of solid obstacles in the channel can manipulate the slip length similar to the variation of slip length with respect to fluid solid interaction potential. These results can act as a guidance to improve the electro kinetic energy conversion efficiency in nanoscale flows which will have immense application in the development of nanofluidic battery.